Environmental Evolution and Human Adaption Recorded From a Salt Production Site at the Coastal Plain of Laizhou Bay, China - Guo, Yuanyuan; Mao, Longjiang; Zhu, Likai; Mo, Duowen (Frontiers in Marine Science, 2022)
The southern coast of the Laizhou Bay is considered as one of important areas for the origin and development of sea salt production in Eastern China. Archaeologists have collected rich materials to better understand history of salt production in the region, but how environmental change influences early salt production is still unknown. Here we collected samples at the Shuangwangcheng (SWC) site in the southern plain of Laizhou Bay. We conducted grain size, mollusk and foraminifera analysis to examine the evolution of sedimentary environment and restored the human adaptions to environmental change. The results showed that the sedimentary environment of study area was lower tidal flat during 6400 5900 yr BP as indicated by coarse and well sorted grain size, high abundance of foraminifera, and the Ammonia beccarii vars. - Quinqueloculina akneriana foraminifera assemblage. Sedimentary environment changed from intertidal to supratidal flat with decreasing abundance of foraminifera and finer upward grain size at 5900 4300 yr BP. After 4300 yr BP, this area was less affected by seawater, which could be reflected by the appearance of freshwater mollusk and rarely discovered foraminifera. Our retrieved environment changes were closely related with ancient human activities. The Holocene transgression constrained the Dawenkou cultural sites within the inland areas with higher altitude. The exposed coast lowlands after sea retreat were initially not suitable for human survival except sporadic salt production sites of the Longshan culture. These conditions were improved during the Shang and Zhou Dynasties when humans widely used the particular natural resources of underground brine for salt production, and then a large number of salt production sites appeared, which made this region develop into an important origin center of salt production. Our research suggests that salt production was an economic activity that was adopted by people to adapt to the harsh environment, which is of great significance for understanding the evolution of the human-environmental relationship in the coastal area.